Amperometric sensor study of the selectivity of poly(vinyl chloride) membranes plasticised with surfactants and liquid crystals - Reddy, S; Gangadharan, B; Manini, J (Elsevier, 2004)
We have characterised a range of modified poly(vinyl chloride) (PVC) membranes based on their permeability and selectivity to electrochemically active species. The species are detected at an amperometric (two-electrode) cell in phosphate buffer solution. Diffusants studied were paracetamol, catechol, ascorbic acid and hydrogen peroxide. Membrane modifying agents studied were cationic (Aliquat 336s) and non-ionic (Tween 80 and Triton X-100) surfactants as well as, for the first time, surfactant combinations with the liquid crystal N-(4-methoxybenzylidene)-4-butylaniline) (NMBB). Results were compared with commercially available and unselective microporous polycarbonate and haemodialysis membranes. The non-ionic surfactant-modified membranes exhibited permeability characteristics comparable to the commercially available membranes. The Aliquat-modified membrane screened out paracetamol and peroxide, while NMBB-only-modified membranes exhibited excellent selectivity against paracetamol but not peroxide or 4-aminophenol (4-AP). Whole blood and protein fouling characteristics of the membranes using bovine serum albumin (BSA) are also reported. The membranes studied have implications for the design of highly selective enzyme-electrode biosensors. © 2003 Elsevier B.V. All rights reserved.